The implementation of an integrated education data system at national level: the Sistema Gestão Presente - Peres, Fabíola; Silva, Carla; Fernandes, Ana Beatriz (Conference on Digital Government Research, 2025)
This article analyzes the implementation of the Sistema Gestão Presente, an initiative of NEES (UFAL) in partnership with the Ministry of Education for the interfederative integration of educational data, with the aim of optimizing data management and supporting educational programs at a national level. This study highlights the main challenges faced during the process of implementing this system, using as a repertoire the discussion about data governance, which has already existed in Brazil for some decades. Based on focus groups, one-on-one meetings, discussion groups and experience reports, the article brings together challenges and strategies in four categories: 'Programa Pé-de-Meia business rules challenges', 'Service challenges', 'Follow-up and monitoring challenges' and 'Technological challenges'.